A study on the release characteristics and formation mechanism of SO2 during co-combustion of sewage sludge and coal slime. (1st February 2023) - Wang, Xin; Xu, Jun; Ling, Peng; An, Xiaoxue; Han, Hengda; Chen, Yifeng; Jiang, Long; Wang, Yi; Su, Sheng; Hu, Song; Xiang, Jun
Highlights: Interaction between the sewage sludge and coal slime during their co-combustion was found. SO2 formation and release mechanism during co-combustion of sewage sludge and coal slime was revealed. AAEMs play a key role on the evolution of S-functional groups. Abstract: The production of sewage sludge (SS) and coal slime (CS) is increasing year by year, which affects the ecological environment and human daily life, and it is urgent to deal with them reasonably. This study investigated the SO2 release characteristics and the evolution of S functional groups and minerals during the combustion of SS, CS and their blends. The results showed that the co-combustion of SS and CS had an interaction on desulfurization. When the temperature was 800 ℃ and the blend ratio of SS was 20%, it was most beneficial to suppress the emission of SO2 . The types of S functional groups in SS and CS were similar but the relative content was different. The evolution of some S functional groups showed various laws. In the early stage of co-combustion, Sulfate (S1) reached maximum value earlier and decreased at the end of co-combustion, and Sulfide (S5) were more likely to be converted to aromatic-S (S4). According to XRD and SEM-EDS results, Ca (mainly CaCO3 ) in the fuels had a significant effect on SO2 release characteristics during the co-combustion. CaO formed by thermal decomposition of CaCO3 could react with SO2 to form intermediate solid products (CaS and CaSO3 ). These intermediates further reacted with O2 to generate CaSO4, thus retaining SO2 in the ash. Some CaSO4 was decomposed in the later stage of combustion, leading the re-release of SO2 . Excessive combustion temperature and reductive gases would lead to the decomposition of CaSO4, which reduced the ability of Ca to absorb SO2 .